2018
DOI: 10.3390/ma11040528
|View full text |Cite
|
Sign up to set email alerts
|

PMMA-g-OEtOx Graft Copolymers: Influence of Grafting Degree and Side Chain Length on the Conformation in Aqueous Solution

Abstract: Depending on the degree of grafting (DG) and the side chain degree of polymerization (DP), graft copolymers may feature properties similar to statistical copolymers or to block copolymers. This issue is approached by studying aqueous solutions of PMMA-g-OEtOx graft copolymers comprising a hydrophobic poly(methyl methacrylate) (PMMA) backbone and hydrophilic oligo(2-ethyl-2-oxazoline) (OEtOx) side chains. The graft copolymers were synthesized via reversible addition-fragmentation chain transfer (RAFT) copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…For example, Muljajew et al have studied the aggregation of graft copolymers comprising a hydrophobic poly(methyl methacrylate) (PMMA) backbone and hydrophilic oligo(2ethyl-2-oxazoline) (OEtOx) side chains (PMMA-g-OEtOx). 57 These copolymer systems enabled formation of micelle structures, which could carry small guest molecules. The authors studied the molar mass of unimeric species, i.e., the polymers in a good solvent for the polymer, and that of micelle structures in water including determination of the partial specific volume, υ. Conclusively, and by making use of intrinsic estimates of s, i.e., [s] (eq 4) and the modified Svedberg equation (right-hand side of eq S5), they found that, depending on the initial polymer composition, the degree of aggregation of polymers could be designed to result in numbers of aggregation up to roughly ten in an aqueous solution.…”
Section: ■ Types Of Auc Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Muljajew et al have studied the aggregation of graft copolymers comprising a hydrophobic poly(methyl methacrylate) (PMMA) backbone and hydrophilic oligo(2ethyl-2-oxazoline) (OEtOx) side chains (PMMA-g-OEtOx). 57 These copolymer systems enabled formation of micelle structures, which could carry small guest molecules. The authors studied the molar mass of unimeric species, i.e., the polymers in a good solvent for the polymer, and that of micelle structures in water including determination of the partial specific volume, υ. Conclusively, and by making use of intrinsic estimates of s, i.e., [s] (eq 4) and the modified Svedberg equation (right-hand side of eq S5), they found that, depending on the initial polymer composition, the degree of aggregation of polymers could be designed to result in numbers of aggregation up to roughly ten in an aqueous solution.…”
Section: ■ Types Of Auc Experimentsmentioning
confidence: 99%
“…For example, Muljajew et al have studied the aggregation of graft copolymers comprising a hydrophobic poly­(methyl methacrylate) (PMMA) backbone and hydrophilic oligo­(2-ethyl-2-oxazoline) (OEtOx) side chains (PMMA- g -OEtOx) . These copolymer systems enabled formation of micelle structures, which could carry small guest molecules.…”
Section: New Applications Of the Auc In The Life Sciencesmentioning
confidence: 99%
“…[50][51][52][53] More complex architectures have also been studied in order to enhance the properties of the final material and have a better control over the temperature range of the phase transition. 19,23,34,54,55 However, despite the large amount of work on 2-oxazoline polymers showing an LCST behaviour, only a limited number of poly(2-alkyl-2-oxazoline)s is reported to show a upper critical solution temperature (UCST) phase transition, which only occurs in alcohol/water mixtures. 52,[56][57][58] In this study, linear homo and copolymers of 2-stearyl-2oxazoline (SteOx) and 2-ethyl-2-oxazoline (EtOx) are synthesized via living CROP resulting in well-defined copolymers with varying oil solubility behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that a significant difference in the nature of the backbone and carbochain side chains determines the amphiphilicity of hybrid brushes owing to the selectivity of components with respect to solvents of different nature. This structural feature is responsible for the segregation of fragments of the graft copolymer in solution and the formation of supramolecular structures which cannot be obtained for polymers with a different architecture [7][8][9][10]. In addition, such brushes are characterized by a significantly rarer grafting of side chains compared to carbonchain molecular brushes, which allows a much more pronounced conformational freedom of both the main and side chains.…”
Section: Introductionmentioning
confidence: 99%